Organization-Based Self-Esteem (OBSE) And Its Influence On Self-Perceived Employability (SPE) Of IT Export Sector Employees In Sri Lanka - Tharanga Sumanasiri, Erabaddage Gishan; Ab Yajid, Mohd Shukri; Khatibi, Ali (European Scientific Journal, ESJ, 2016)
The sense of value organizational members demonstrate in their workplace influences employee commitment, performance, productivity, and even absenteeism. The concept of Organization Based Self-Esteem (OBSE) reflects the self-efficacy of organization members and has become a popular research topic in Organization Behavior and Psychology. While there are many prior findings about how OBSE influence the ultimate employability of employees, the lack of clear definition and operationalization of the employability concept has negatively influenced knowledge development. The concept of Self-Perceived-Employability (SPE) has been introduced as an alternative concept to operationalize employability in a clear and measurable manner. There is evidence to show the relationship between OBSE and SPE but they are mainly theoretical and qualitative in nature, while there is little research evidence that quantifies the OBSE and SPE link. The current research paper brings quantitative research evidence to understand the association between two very important factors that influence organizational performance in IT export sector, fast growing service industry in Sri Lanka. The study explains the findings of self-administered questionnaires done on 372 employees in Sri Lankan IT export sector. Data analysis done using quantitative statistical analysis methods, while reliability analysis was performed to ensure the internal consistency of OBSE and SPE. The correlation analysis revealed a strong and positive correlation between OBSE and SPE, and confirms the earlier notion that OBSE influences SPE.